The Interaction between Accrual Management and Hedging: Evidence from Oil and Gas Firms - Pincus, Morton; Rajgopal, Shivaram (The Accounting Review, 2002)
This research investigates whether oil and gas producing firms use abnormal accruals and hedging with derivatives as substitutes to manage earnings volatility. Firms engaged in oil exploration and drilling are exposed to two kinds of risks that can cause earnings volatility: oil price risk and exploration risk. Firms can use abnormal accrual choices and/or derivatives to reduce earnings volatility caused by oil price risk, but cannot directly hedge the operational risk of unsuccessful drilling. Because hedging and using abnormal accruals are costly activities, and because prior research suggests managers do not eliminate all volatility (Haushalter 2000; Barton 2001), we expect that, at the margin, managers will use these smoothing mechanisms as substitutes to manage earnings volatility. Our results suggest a sequential process whereby managers of oil and gas producing firms first determine the extent to which they will use derivatives to hedge oil price risk, and then, especially in the fourth quarter, manage residual earnings volatility by trading off abnormal accruals and hedging with derivatives to smooth income.